FORMATION OF THE FINANCIAL AND INVESTMENT POTENTIAL OF THE ENTERPRISE FROM THE POSITION OF A STRATEGIC APPROACH - DOTSENKO, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes approaches to the concepts of "financial potential" and "investment potential", reveals their content and features. Based on the results of a critical analysis of scientific sources, it is justified that the financial and investment potential of the enterprise must be considered as a single definition, which is determined by a set of general characteristics. Based on the conducted research, the author's definition of the concept of "financial and investment potential" of an enterprise is proposed. The financial and investment potential of an enterprise is the ability of an enterprise to accumulate a set of internal and external financial and investment resources, to use them as efficiently as possible for the purpose of obtaining economic benefits, to ensure strategic and tactical development goals. It has been proven that the financial and investment potential of a business entity has a number of varieties. The classification features of the financial and investment potential of the business entity are singled out, namely: according to the time required to achieve a certain value of the financial and investment potential of the business; depending on the degree of realization of the financial and investment potential of the business entity; depending on the method of obtaining information necessary for assessing the financial and investment potential of the business entity; on the basis of the expected results of the realization of the financial and investment potential of the enterprise. The classification of factors affecting the financial and investment potential of a business entity is generalized. The sequence of development and implementation of the strategy for the formation of the financial and investment potential of the enterprise is proposed. It determines the priority directions of development, the sources of investment resources and the sequence of stages of realization of long-term financial and investment goals, which ensure the overall development of the enterprise's activities in the future. The formation of the financial and investment potential of the enterprise in the strategic perspective is aimed at restoring the stable state of enterprises, including as a result of investment. And it includes the effect of the joint action of financial and investment resources, combining current and strategic goals with the possibility of attracting internal and external sources for financial support of the enterprise's investment activities.
Keywords: financial potential; investment potential; financial and investment potential; the strategy of forming the financial and investment potential of the enterprise